Positive behaviour support: What model of disability does it represent?. Issue 3 (2nd July 2016) - Grey, Ian; Lydon, Helena; Healy, Olive
ABSTRACT: Positive behaviour support (PBS) has become well established as an intervention approach for individuals with intellectual disability and challenging behaviour. However, what remains unexplored is the relationship between PBS and the medical and social models of disability, which historically are the dominant conceptual frameworks put forward in understanding disability. This paper identifies the difficulties in exploring this relationship due to the often simplistic portrayals of such models. Though PBS has a change agenda, typically a characteristic of the medical model, it is change at an ecological level that is central to PBS. An analysis of the practices of PBS demonstrates a concern with pragmatically identifying the interaction between person and environment to reduce the occurrence of challenging behaviour. PBS practices are considered to be more aligned with a supports model because they build an individual ecology of support tied to meaningful quality of life outcomes for individuals with challenging behaviour.